Efficacy and Safety of Transbrachial Access for Iliac Endovascular Interventions. (June 2016) - Stavroulakis, Konstantinos; Usai, Marco V.; Torsello, Giovanni; Schwindt, Arne; Stachmann, Arne; Beropoulis, Efthymios; Bisdas, Theodosios
Purpose: To evaluate the use of a brachial artery access for endovascular treatment of iliac artery disease.Methods: A retrospective review was conducted of 201 patients (mean age 73 years; 147 men) treated via a brachial artery access for iliac artery stenosis. The majority (n=141, 70%) presented with lifestyle-limiting claudication (Rutherford category 3), whereas the incidence of critical limb ischemia (Rutherford categories 4–6) was 30% (n=70). Diagnostic angiography revealed a TransAtlantic Inter-Society Consensus II (TASC) C/D lesion in 114 (57%) patients. The primary outcome was technical success achieved exclusively with a brachial artery access. Secondary outcomes were secondary technical success (adjunctive transfemoral access), access site complications, and stroke/transient ischemic attack (TIA).Results: In 17 (8%) patients, lesion crossing was unsuccessful, while an adjunctive transfemoral approach was necessary to restore iliac vessel patency in 23 (11%) cases. Thus, the primary and secondary technical success rates were 81% and 92%, respectively. Local hematomas (9, 4%) dominated the access site complications, followed by pseudoaneurysms (8, 4%), late brachial artery bleeding (4, 2%), brachial artery occlusion (2, 1%), and puncture site infection (2, 1%). No transient or permanent median nerve dysfunction was observed. The stroke/TIA rate was 2% (n=4). A single patient died due to acute coronary syndrome (0.5% mortality). TASC II class (p=0.58), sex (p=0.66), and target vessel (p>0.3 for all locations) had no effect on technical success. Female gender unfavorably influenced the incidence of access site complications (hazard ratio 6.7, 95% confidence interval 2.7 to 15, p<0.001), but sheath size did not (p=0.22).Conclusion: Brachial artery access enables endovascular treatment of iliac artery disease in the majority of patients, although an adjunctive transfemoral access may be required. However, the high incidences of access site complications and cerebral events remain a significant limitation of the transbrachial approach.